Al-Mawād at-Ta‘līmīyyah ‘alā Asās al-Kifāyah al-Ittiṣāliyyah fī al-Kitāb al-Madrasī “Al-‘Arabiyyah al-Mu‘āṣirah” li Eckehard Schulz - Furaida Ayu Musyrifa; Wildana Wargadinata; Nur Ila Ifawati; Khabibi Muhammad Luthfi (Lughawiyyat: Jurnal Pendidikan Bahasa dan Sastra Arab, 2021)
Abstract One of the textbooks used in different countries written by non-Arabs is "Modern Standard Arabic" by Schulz. By the author, he allegedly used a communicative input. However, in terms of strategic competence and the perspective of the foundations of the preparation of educational materials, it was not enough. Based on this issue, the objectives of this research are to know the foundations of the teaching materials in the textbook "Modern Standard Arabic" by Schulz, and its educational materials from the perspective of communicative competence. This research used the synthetic-inferential approach with the theory of foundations for preparing educational materials and the theory of communication. The type of this research is qualitative-quantitative through a desk study, which is written data and taken from the textbook "Modern Standard Arabic" by Schulz, whether it was printed or electronic version. The data collection used the documentation method, and the data analysis used the James Spradley method and discourse analysis. The results obtained by the research are the foundations for the preparation of the textbook, "Modern Standard Arabic" by Schulz, which is the structural-communicative approach; purposes; Material consisting of its selection, organization, arrangement and presentation; ways; and evaluation, and the educational material in that book is a perspective of communicative competence is very good which is up to 85.45%. Keywords: Educational Materials, Modern Standard Arabic, communicative competence